2008
DOI: 10.1007/s11999-008-0354-9
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Axial Rotation in Mobile-bearing Knee Designs

Abstract: It has often been assumed rotational kinematics are improved with mobile-bearing TKA designs as the terms mobile-bearing and rotating platform imply. We tested this assumption by assessing the in vivo axial rotation magnitudes and patterns of 527 knees implanted with 12 different mobile-bearing TKA designs. Implants were grouped and compared by type-posterior stabilized (PS), posterior cruciate retaining (PCR), and posterior cruciate sacrificing (PCS)-and by specific design. We hypothesized all three mobile-be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 19 publications
1
21
0
1
Order By: Relevance
“…However, the reason for this temporal difference between the two groups is unclear, although we suspect motion of the polyethylene insert in the FP prosthesis may have reduced after 12 months, whereas the post-cam mechanism of the RP/PS prosthesis assured femoral rollback even after 12 months. This explanation is supported by the findings of a recent study, which found polyethylene rotation in mobile-bearing systems reduces in vivo after implantation [30]. The reduced polyethylene rotation might affect maximum flexion adversely.…”
Section: Discussionsupporting
confidence: 63%
“…However, the reason for this temporal difference between the two groups is unclear, although we suspect motion of the polyethylene insert in the FP prosthesis may have reduced after 12 months, whereas the post-cam mechanism of the RP/PS prosthesis assured femoral rollback even after 12 months. This explanation is supported by the findings of a recent study, which found polyethylene rotation in mobile-bearing systems reduces in vivo after implantation [30]. The reduced polyethylene rotation might affect maximum flexion adversely.…”
Section: Discussionsupporting
confidence: 63%
“…These findings demonstrate the introduction of a second conforming bearing surface in mobile-bearing TKAs does not improve the wear damage behavior and must be considered another argument against the superiority of these implants compared to conventional fixedbearing TKAs. Despite the fact that in vivo studies of patients with mobile-bearing knees using static radiographic and dynamic fluoroscopic studies [3,17] show motion at the mobile-bearing surface during daily activities, this motion has not led to improved clinical outcomes or increased survivorship at followup times out to 23 years [12]. Our retrieval data serve to further question the use of this design, since it does not appear to reduce wear damage.…”
Section: Discussionmentioning
confidence: 86%
“…Increased normal axial rotation leads to better patellofemoral tracking and improved extensor mechanism mechanics [2,3,5,7,8,16,27]. However, the overall magnitudes of axial rotation were well below those observed in normal knees and were similar in magnitudes reported by Wasielewski et al [29]. Finally, femoral-PE rotational congruency results in the femoral cam contacting the center of the PE post more consistently during flexion [30].…”
Section: Discussionmentioning
confidence: 54%
“…Another study also validated the occurrence of bearing mobility but showed that TKAs with mobile-bearing prostheses do not necessarily increase the amount of in vivo axial rotation compared with TKAs with fixed-bearing prostheses and that the overall in vivo axial rotation magnitudes remain substantially lower for TKAs compared with normal knees [29]. Unfortunately, most of these studies have relatively short followups.…”
mentioning
confidence: 95%